BELT AND ROAD INITIATIVE: CHINA'S GEROPOLITICAL IMPLICATIONS IN ASIA - Kunkunrat Kunkunrat (Fox Justi : Jurnal Ilmu Hukum, 2023)
The Belt and Road Initiative/BRI as an ambitious infrastructure development initiative which is a continuation of the Silk Road program, has played a central role in restructuring the economic and political landscape in a number of countries in Asia. This research aims to investigate the geopolitical implications that the People's Republic of China's BRI has in the Asian region. The research methodology uses a qualitative approach with descriptive methods. The research results show that China's Belt and Road Initiative (BRI) has had a major impact on Asian geopolitics. This initiative increases China's economic and political influence in the region, strengthens connectivity between countries, and opens new trade routes. Although it brings economic opportunities, the BRI also poses a number of challenges, including financial risks, political risks and socio-environmental impacts. BRI's success is not only measured by economic growth, but also by its impact on regional stability and sustainability. Therefore, continuous attention is needed to ensure that the implementation of the BRI is in line with the principles of justice, transparency and sustainability, so that it can provide long-term benefits for the entire Asian region.